(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The research dealt with ashort translation of Imam Zaki al-DinAbi Muhammad Abd al-Azim ibn Abd al-Qawi al- mundhiri. He reveald his method of improving the hadiths with evidence that was agreed upon by al-Bukaari and Muslim or with more than one witness in al-Saheehayn. The search also revealed the navigation of Imam al-Manzari in modern science and his high accuracy in criticizing the hadiths.